PENERAPAN STRATEGI PEMBELAJARAN MIND MAPPING UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI PESERTA DIDIK KELAS XI MIPA 6 SMA NEGERI 1 KUTA UTARA - Ni Kadek Mesy Wulandari; Ni Kadek Rini Purwati (Emasains : Jurnal Edukasi Matematika dan Sains, 2023)
Abstract This study aims to determine whether the application of the Mind Mapping learning strategy can improve the learning outcomes of students in class XI MIPA 6 SMA Negeri 1 Kuta Utara on excretion system material. This research was carried out against a background of students' low understanding of biology learning material. This can be seen from the results of daily assessments in the initial conditions (pre cycle) where as many as 77% of students scored below the KKM with the average student score at 61 and the percentage of learning completeness at 23%. Based on these problems, research on the application of Mind Mapping learning strategies was carried out to improve biology (excretory system) learning outcomes students in class XI MIPA 6 SMA Negeri 1 Kuta Utara. This research is a type of classroom action research using 2 cycles, where each cycle is carried out in four stages consisting of (1) action planning, (2) action implementation. (3) observation, and (4) reflection. The results showed that there was an increase in biology learning outcomes, especially in the excretory system material by applying the Mind Mapping learning strategy. Based on the results of the study, it was found that there was a change in the average score of students' learning outcomes, from initially 61 to 80, and finally reached 84. In addition, the percentage of students' learning completeness also increased, which was originally 23% in the initial conditions then increased to 64% in the second cycle. I and 73% in cycle II. Keywords: Mind Mapping, Learning Outcomes, Active Learning, Students Concept Understanding, Biology